Forest transition in South Korea: reality, path and drivers - Bae, J.S.; Joo, R.W.; Kim, Y.S. (Elsevier, 2012)
While forest transition (FT) in South Korea began in 1955, when forest cover was only 35% of national land area, significant increases in both forest cover and growing stock really occurred in the early 1970s. Using reconstructed historical records, we empirically demonstrate that (1) FT in South Korea was mainly accomplished by the recovery of degraded, non-stocked forest; and (2) one-dimensional FT analysis using forest area alone has severe limitations in diagnosing meaningful changes in forest sustainability. The key driver of FT in South Korea was the government-led reforestation policy. The comprehensive reforestation plans, started in 1973, not only provided economic incentives to the general public by establishing clear quantifiable goals, they also promoted inter-agency cooperation and coordination, especially between the energy and forest sectors, to replace firewood with fossil fuels. These government-led efforts, accompanied by rural–urban migration, brought an increase in stocked forest area and a complementary rising average growing stock level. The case of South Korea shows that FTs can be cultivated in a relatively short period of time by a central authority, even with imperfect governance and low economic development.